Evaluation of the food safety knpwledge, attitude, and practices of cafeteria food handlers in the University of the Philippines Visayas-Miagao, Campus. - Hosillos, Lara Angelica De La Cruz (2023.)
Over the last two decades, school cafeterias have been identified as one of the top sources of foodborne disease outbreaks (FBDO) in the Philippines. It has been demonstrated that the hands of food service personnel are vectors for transmitting FBDOs because of poor personal hygiene. Using a structured food safety questionnaire, this study assessed the food safety knowledge, attitude, and practices (KAP) of cafeteria food handlers at the University of the Philippines Visayas - Miagao Campus. The total plate count (TPC) method and Staphylococcus aureus (S. aureus) determination were used to evaluate the viable microbial population on the hand surface of food handlers. It was determined that the participants had adequate knowledge and a positive attitude toward food safety in the workplace but inadequate observance of food safety practices. The highest bacterial count in the hand samples was 1.45x104 cfu/in2, exceeding the maximum permissible limit of 32 cfu/in2 for food contact surfaces. Similarly, S. aureus was detected in at least 5 out of 15 food handlers per sampling period conducted. The Chi-Squared test of association yielded p-values of 0.312 for S. aureus and 0.282 for TPC. Statistical analyses show no significant relationship between the food safety KAP and the microbial features on the hand surface of food handlers in UPV Miagao.
Thesis (Undergraduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Food safety -- Cafeteria -- University of the Philippines Visayas